THE USE OF CEMARA UDANG (Casuarina equisetifolia) FOR AGRICULTURAL PURPOSES IN THE SOUTHERN COAST OF YOGYAKARTA - Atus Syahbudin; Dwi Tyaningsih Adriyanti; Anisa Handayani; Hu Bai; Katsuya Osozawa; Ikuo Ninomiya (UNEJ e-Proceeding, 2012)
An exploration along the Southern Coast of Yogyakarta and deep interview with276 respondents in the Southern Coast of Kulon Progo and Gunungkidul Regencies hadbeen conducting during January 2010 and February-May 2012. Respondents recognizedthat before the establishment of Casuarina equisetifolia they faced problems like strongwind in the agricultural land (81.6%), uncultivated land near the coast (20.3%), agriculturecrops die because of salt water (17%), and others (11.3%). During 16 years theestablishment of C. equisetifolia has been creating vegetative wind barrier due to Attims'tree architecture model. C. equisetifolia reduces the use of dried coconut leaf/blarak(29.3%) and objectifies green coastal landscape, which makes farmer, fisherman,inhabitant, visitor and merchant become pleasant. In addition, C. equisetifolia providesbenefits as shady tree for agricultural nursery (10.9%), mulch (10.4%), fertilizer (3.3%),and many kinds (49.4%). Reduction in the use of blarak, mulch and purchased fertilizerwill increase farmer’s income because the cost of labor, fertilizer and mulch decrease.